2013
DOI: 10.3892/ol.2013.1579
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of miR-34c-3p and miR-34c-5p on the proliferation, apoptosis and invasion of glioma cells

Abstract: Glioblastoma is the most malignant and common intrinsic brain tumor, but the molecular mechanism of glioma pathophysiology is poorly understood. Recent data have shown that microRNAs regulate the expression of several genes associated with human cancer. In the present study, the function of miR-34c in glioma cells was analyzed. It was demonstrated that miR-34c-3p and miR-34c-5p were downregulated in gliomas, by performing qPCR on tumor tissues from glioma patients and glioma cell lines, compared with normal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 26 publications
0
62
0
1
Order By: Relevance
“…Pattern C miRNAs seem to contribute to the df/df mouse longevity by a CR‐independent mechanism. Recent reports demonstrate tumor suppressor (Wu et al ., 2013) and neuroprotective (Minones‐Moyano et al ., 2011) functions for these miRNAs. Wu and colleagues found downregulation of miR‐34c‐3p/5p in glioma tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pattern C miRNAs seem to contribute to the df/df mouse longevity by a CR‐independent mechanism. Recent reports demonstrate tumor suppressor (Wu et al ., 2013) and neuroprotective (Minones‐Moyano et al ., 2011) functions for these miRNAs. Wu and colleagues found downregulation of miR‐34c‐3p/5p in glioma tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues found downregulation of miR‐34c‐3p/5p in glioma tissue. Overexpression of these two miRNAs in glioma cell lines inhibited the cell proliferation, cell cycle changes, apoptosis, and cell invasion (Wu et al ., 2013). We found that predicted targets of the pattern C GbA miRNAs are significantly enriched in the MAPK signaling pathway (Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from p27, miRNAs are one of the most common regulatory factors in NPC [4951], and they play physiological and pathophysiological roles in cell proliferation, differentiation and apoptosis by regulating protein expression in a post-transcriptional manner [52, 53]. Wu et al [54] identified miR-30d as a tumor suppressor, which was regulated by a new AKT/FOXO/miR-30d/MTDH signaling transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The family of miR-34, including miR-34a, b and c, has been reported to regulate numerous cellular events, including the cell cycle, cell migration and apoptosis (38,39). miR-34c has two identified mature miRNAs: miR-34c-3p and miR-34c-5p (40,41). Previous studies have indicated that miR-34c has tumor-suppressive effects, and suppresses the cell cycle primarily by induction of G1 cell cycle arrest (42).…”
Section: Discussionmentioning
confidence: 99%